2004
DOI: 10.1124/mol.65.3.611
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Brain Nicotinic Acetylcholine Receptors in the Rat during Long-Term Self-Administration of Nicotine: Disproportionate Increase of the α6 Subunit

Abstract: In male rats continually self-administering nicotine (approximately 1.5 mg free base/kg/day), we found a significant increase of nicotinic acetylcholine receptors (nAChRs) labeled by epibatidine (Epb) in 11 brain areas. A large increase of highaffinity Epb binding sites was apparent in the ventral tegmentum/substantia nigra, nucleus tractus solitarii, nucleus accumbens, thalamus/subthalamus, parietal cortex, hypothalamus, and amygdala. A smaller but significant up-regulation of highaffinity Epb sites was seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 48 publications
(78 reference statements)
13
76
4
1
Order By: Relevance
“…Our laboratory and others have shown, using this prolonged access model (Valentine et al, 1997;Fu et al, 2001Fu et al, , 2003Brower et al, 2002;LeSage et al, 2002LeSage et al, , 2003LeSage et al, , 2006Parker et al, 2004), that adult rats will acquire nicotine SA in the absence of food deprivation or prior food-reinforced conditioning. For several reasons, this prolonged access model is advantageous for studying nicotine SA in rats during midadolescence.…”
Section: Adolescent Nicotine Self-administration H Chen Et Almentioning
confidence: 82%
“…Our laboratory and others have shown, using this prolonged access model (Valentine et al, 1997;Fu et al, 2001Fu et al, , 2003Brower et al, 2002;LeSage et al, 2002LeSage et al, , 2003LeSage et al, , 2006Parker et al, 2004), that adult rats will acquire nicotine SA in the absence of food deprivation or prior food-reinforced conditioning. For several reasons, this prolonged access model is advantageous for studying nicotine SA in rats during midadolescence.…”
Section: Adolescent Nicotine Self-administration H Chen Et Almentioning
confidence: 82%
“…As reported previously (Brower et al, 2002;Parker et al, 2004;Valentine et al, 1997), SD and Lewis rats acquired nicotine (0.03 mg/kg) SA without prior training, priming or food deprivation when the drug was available 23 h/day. Similar levels of nicotine SA were achieved by the rats used throughout these experiments.…”
Section: Nicotine Samentioning
confidence: 84%
“…Rodent studies have shown that intravenous nicotine self-administration leads to an increase in the number of α6* receptors in rats [114], but a decrease in the number of striatal α6* receptors in rodents chronically treated with nicotine by means of minipumps [115,116] or receiving it in drinking water [117]. These apparently discrepant results may be due to the different modalities of nicotine administration leading to differences in nicotine concentration in the brain and/or the kinetics or duration of receptor exposure, which may differently affect α6* nAChRs.…”
Section: Regulation Of Native Subtypes By Chronic Nicotine Exposurementioning
confidence: 99%